Cushing's disease presenting with avascular necrosis of the femoral heads and complicated by pituitary apoplexy. Issue 10 (October 1987) - Wicks, I P; Calligeros, D; Kidson, W; Bertouch, J V
Abstract : A case of Cushing's disease presenting with avascular necrosis of the femoral heads is described. Eighteen months after the onset of hip symptoms the patient developed pituitary apoplexy and presented to hospital as a medical emergency. Endogenous hypercortisolism is a rare and important cause of avascular necrosis of bone.